2021
DOI: 10.1128/aem.02171-20
|View full text |Cite
|
Sign up to set email alerts
|

YbeY Controls the Type III and Type VI Secretion Systems and Biofilm Formation through RetS in Pseudomonas aeruginosa

Abstract: YbeY is a highly conserved RNase in bacteria and plays essential roles in the maturation of 16S rRNA, regulation of small RNAs (sRNAs) and bacterial responses to environmental stresses. Previously, we verified the role of YbeY in rRNA processing and ribosome maturation in Pseudomonas aeruginosa and demonstrated YbeY-mediated regulation of rpoS through a sRNA ReaL. In this study, we demonstrate that mutation of the ybeY gene results in upregulation of the type III secretion system (T3SS) genes as well as downre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…Transcriptomic analyses in the opportunistic bacteria Pseudomonas aeruginosa revealed that the deletion of ybeY gives rise to downregulation of catalase genes with increased susceptibility to oxidative stress (Xia et al, 2020a). A subsequent study further revealed the pleiotropic roles of YbeY and YbeYmediated regulation in adapting to environmental stress, which was found to be associated with bacterial virulence (Xia et al, 2020b). In P. aeruginosa, E. coli, and S. aureus, the ybe operon contains the ybeY and ybeZ genes with ATP binding and a nucleoside triphosphate hydrolase domain (Butland et al, 2005;Vercruysse et al, 2016;Wood et al, 2019).…”
Section: Introductionmentioning
confidence: 93%
“…Transcriptomic analyses in the opportunistic bacteria Pseudomonas aeruginosa revealed that the deletion of ybeY gives rise to downregulation of catalase genes with increased susceptibility to oxidative stress (Xia et al, 2020a). A subsequent study further revealed the pleiotropic roles of YbeY and YbeYmediated regulation in adapting to environmental stress, which was found to be associated with bacterial virulence (Xia et al, 2020b). In P. aeruginosa, E. coli, and S. aureus, the ybe operon contains the ybeY and ybeZ genes with ATP binding and a nucleoside triphosphate hydrolase domain (Butland et al, 2005;Vercruysse et al, 2016;Wood et al, 2019).…”
Section: Introductionmentioning
confidence: 93%
“…Indeed, while the interactions of YbeY with ribosomal components are extensively characterised across various species (see below), there is little evidence of its direct association with protein-coding or regulatory RNAs [33,34]. Instead, a few studies exposed amazingly complex and meandering regulatory cascades underlying some of ΔybeY phenotypes [19,32,35]. Pervasive gene expression changes often arise when regulators, such as transcription factors or sRNAs, get involved.…”
Section: Molecular Phenotypes Of Ybey Deficiency: Defective Ribosomes With Far-reaching Consequencesmentioning
confidence: 99%
“…In Pseudomonas aeruginosa, YbeY loss curtails the production of the key σ-factor RpoS, which is responsible for the expression of virulence and stress response genes [19]. In the same organism, a complex cascade involving the posttranscriptional regulators of the Rsm system mediates the upregulation of the type 3 and the downregulation of the type 6 secretion system upon ybeY deletion, resulting in high cytotoxicity and low biofilm formation [35]. Thus, by affecting the levels of just a few positive and negative regulators, YbeY deficiency can lead to impressive genome-wide gene expression changes and pleiotropic phenotypes (Fig.…”
Section: Molecular Phenotypes Of Ybey Deficiency: Defective Ribosomes With Far-reaching Consequencesmentioning
confidence: 99%
See 2 more Smart Citations